Recognition of microplastics suspended in seawater via refractive index by Mueller matrix polarimetry. (March 2023) - Li, Jiajin; Liu, Hongyuan; Liao, Ran; Wang, Hongjian; Chen, Yan; Xiang, Jing; Xu, Xiangrong; Ma, Hui
Abstract: Microplastics have become the marine pollution posing a human health risk, but they are difficult to be detected and recognized for different materials, irregular shapes, and broad size distributions. Microplastics' refractive index (RI) is related to the materials and can be characterized by the Mueller matrix. In this work, the particles are suspended in water and their Mueller matrices are measured by a particulate Mueller matrix polarimetry setup. Four kinds of spherical particles including microplastics are effectively classified by their Mueller matrices. Moreover, two kinds of common microplastics with broad size distributions, irregular shapes, and random orientations are also well recognized by the Mueller matrix. These results imply that RI plays a vital role in the recognition of microplastics suspended in water. By using the Mie theory and discrete dipole approximation simulation, the discussions explain in physics origin how RI affects Mueller matrix coupling with size and structure, and give some decoupling methods. Results in this work help advance future tools to in situ recognize the microplastics in seawater. Highlights: Different microplastics can be well recognized by the Mueller matrix. Refractive index plays a vital role in the recognition of suspended microplastics. Future prototype of particulate Mueller matrix polarimetry can potentially in situ recognize microplastics in seawater.